2022
DOI: 10.1002/smll.202107534
|View full text |Cite
|
Sign up to set email alerts
|

Brain‐Penetration and Neuron‐Targeting DNA Nanoflowers Co‐Delivering miR‐124 and Rutin for Synergistic Therapy of Alzheimer's Disease

Abstract: tau hyperphosphorylation, mitochondrial dysfunction and oxidative stress, and neuroinflammatory response. [3] Among them, the amyloid theory that focuses on excessive deposition of β-amyloid (Aβ) has been extensively studied with wide acceptance. [4] In this theory, imbalance of Aβ metabolism and catabolism in the central nervous system (CNS) has been regarded as the main reason for AD-like pathology. [5] Aβ is the product of a proteolytic process of a transmembrane protein, amyloid precursor protein (APP), by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 85 publications
(86 reference statements)
0
16
0
Order By: Relevance
“…The DF were prepared according to our previous report [39], in which the circular DNA template was first ligation by T4 ligase, followed by rolling circle amplifications (Fig. 1A).…”
Section: Preparation and Characterizations Of Ch/dfmentioning
confidence: 99%
See 1 more Smart Citation
“…The DF were prepared according to our previous report [39], in which the circular DNA template was first ligation by T4 ligase, followed by rolling circle amplifications (Fig. 1A).…”
Section: Preparation and Characterizations Of Ch/dfmentioning
confidence: 99%
“…Recently, we and other groups have demonstrated that DNA nanoflower (DF) is a type of highly robust nanocarrier to deliver functional nucleic acids [39,40]. DF is a spherical porous DNA nanostructure formed by rolling circle amplification (RCA).…”
Section: Introductionmentioning
confidence: 99%
“…The BBB-crossing ability of SC@COF-T5 was assessed by using an in vitro BBB model based on brain endothelial cell lines, in which bEnd.3 cells were cultured in the upper chambers of a transwell dish, and SVG cells were at the bottom of the upper chambers (Figure C). After 5 days, transendothelial electrical resistance (TEER) was measured to be higher than 200 ohm·cm 2 , which suggested that the BBB model was established successfully. Then, RB-modified SC@COF and SC@COF-T5 were added into the apical chamber, and the concentrations of the two nanoparticles were detected after 12, 18, and 24 h of the addition. The permeability of SC@COF-T5 significantly increased compared to that without T5 modification (Figure D), demonstrating that the KLVFF peptide can improve BBB penetration efficiency by bonding RAGE, the receptor for advanced glycation end products.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have confirmed that in the brain tissue or serum of AD patients, many miRNAs have been identified as down-regulated and thought to be involved in the formation of senile plaques and neurofibrillary tangles [ 11 ]. Some brain-enriched miRNAs, such as miR-124, miR-125b, and miR-132 [ 12 14 ], have been revealed to show therapeutic effects on AD. In our previous study, we investigated the changes of miRNA levels in serum of AD patients and found that miR-22-3p was significantly down-regulated [ 15 ].…”
Section: Introductionmentioning
confidence: 99%